Children’s Family Dinner Experiences and Attitudes - Pescud, M.; Pettigrew, Simone (Journal of Research for Consumers, 2010)
Overweight and obesity are a major problem affecting children in many countries. The practice f sharing regular family meals has been shown to improve children’s diets and eating habits, which in turn can have favourable outcomes for children’s weight status. This study explored children’s family mealtime attitudes and experiences to identify themes that may be effective in encouraging families to have regular family meals. Most of the children showed a strong preference to eat together as a family. They reported usually enjoying the interaction with their parents and other family members that occurred during mealtimes. Among the minority who reported that they didn’t enjoy family meals, conflict with siblings and parents was a common explanation. The study findings can inform the development of social marketing campaigns aiming to improve children’s diets and eating behaviours in an effort to prevent and address child obesity.